2012
DOI: 10.2478/s13382-012-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

Indirect costs in patients with coronary artery disease and mental disorders: A systematic review and meta-analysis

Abstract: The aim of the present study was to systematically review the association of comorbid mental disorders with indirect health care costs in patients with coronary artery disease (CAD). A comprehensive database search was conducted for studies investigating persons with CAD and comorbid mental disorders (Medline, EMBASE, PsycINFO, Psyndex, EconLit, IBSS). All studies were included, which allowed for a comparison of indirect health care costs between CAD patients with comorbid mental disorders and CAD patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 42 publications
1
20
0
4
Order By: Relevance
“…Three similar systematic reviews reported substantially higher incremental costs in patients with diabetes, coronary artery disease and asthma [4][5][6]. One explanation for the lower incremental costs associated with mental disorders in CBP patients could be that psychological and antidepressant drug treatments are already standard interventions in the treatment of CBP, which might help to bridge the gap between physical and mental health care [36][37][38].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Three similar systematic reviews reported substantially higher incremental costs in patients with diabetes, coronary artery disease and asthma [4][5][6]. One explanation for the lower incremental costs associated with mental disorders in CBP patients could be that psychological and antidepressant drug treatments are already standard interventions in the treatment of CBP, which might help to bridge the gap between physical and mental health care [36][37][38].…”
Section: Discussionmentioning
confidence: 95%
“…Indirect costs such as work absenteeism represents a majority of overall costs associated with CBP [1,2]. Systematic reviews on costs in patients with other medical diseases than CBP reported substantially increased direct and indirect costs in medically ill patients with comorbid mental disorders [4][5][6].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies have demonstrated that job satisfaction is an important factor influencing workers' health [25,26] and also professional outcomes, such as increased absenteeism and turnover, and decreased performance and motivation [27][28][29]. Moreover, previous studies have clearly demonstrated that occupational stress and mental distress make a significant contribution to the risk of CHD and, therefore, preventive interventions may benefit both RTW process and cardiac prognosis [2,[40][41][42]. In view of the influence of job satisfaction on the RTW process, it is important to understand which factors produce job satisfaction among employees who return to work after a long-term period of sick leave due to cardiac health problems.…”
Section: Association Between Baseline Predictors and Job Satisfactionmentioning
confidence: 99%
“…It accounts for 1.8 million deaths each year, and involves major economic costs as well as human costs for Europe [1]. In recent decades, thanks to advances in diagnostic and therapeutic procedures, and thanks to improvement in rehabilitation programs, death rates have been falling and the prevalence of older workers with CHD, after a surgery/rehabilitation, has been consistently and constantly increasing [2]. The main goal of cardiac rehabilitation (CR) is to facilitate the return to social and professional life as similar as…”
Section: Introductionmentioning
confidence: 99%